An individualised nutritional intervention concept for nursing home residents with or at risk of malnutrition: An enable study - Seemer, Johanna; Kiesswetter, Eva; Blawert, Anne; Fleckenstein, Daniela; Gloning, Marina; Bader-Mittermaier, Stephanie; Sieber, Cornel; Wurm, Susanne; Volkert, Dorothee (Geriatrics, 2021)
Dietary intake and requirements in nursing home (NH) residents vary individually, but concepts for individualised interventions are currently lacking. Therefore, we present an individualised modular nutritional intervention concept for NH residents with (risk of) malnutrition and describe its application and acceptability. Three enrichment modules-a sweet and a savoury protein cream (40 g, 125 kcal, 10 g protein) and a protein-energy drink (250 mL, 220 kcal, 22 g protein)-were offered to residents of two German NHs single or in combination in five levels of enrichment from level 0 (no enrichment) to 4 (all enrichment modules) to compensate for individual energy and protein deficiencies. Residents with chewing and/or swallowing difficulties received reshaped instead of usual texture-modified meals. The intervention concept was applied to 55 residents (Mean age of 84 ± 8 years, 76.0% female, 25.5% malnutrition). Despite (risk of) malnutrition, 18.2% received no enrichment (level 0). Level 1 was allocated to 10.9%, level 2 to 27.3%, level 3 to 20.0% and level 4 to 23.6% of the residents. 32.7% received reshaped texture-modified meals (RTMM). Participants consuming RTMM were more often assigned to level 4 than residents receiving usual meals (38.8% vs 16.2%). We proposed and successfully applied an individualised modular nutritional intervention concept to NH residents with (risk of) malnutrition. In the next step, the effects of the concept and its transferability to other NHs need to be demonstrated.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Enable-cluster; Individualised intervention; Malnutrition; Nursing home; Oral nutritional supplement; Texture-modified diet

Effects of an individualised nutritional intervention to tackle malnutrition in nursing homes: a pre-post study - Seemer, Johanna; Kiesswetter, Eva; Fleckenstein-Sussmann, D.; Gloning, M.; Bader-Mittermaier, S.; Sieber, Cornel; Sixt, B.; Wurm, S.; Volkert, Dorothee (European Geriatric Medicine, 2021)
Purpose: Individualised interventions are recommended to tackle malnutrition in older adults, but approaches for nursing home (NH) residents are scarce. This study investigated the effects of an individualised nutritional intervention in NH residents with (risk of) malnutrition. Methods: In a pre-post study, 6 weeks (w) of usual care were followed by 6w of intervention. The intervention consisted of up to three supplement modules (sweet and savoury protein creams and protein-energy drink, single or combined) and, if required, reshaped texture-modified meals (RTMM). Results: Fifty residents completed the study (84 ± 8 years, 74% female). One-third (32%) received RTMM. Additional 258 ± 167 kcal/day and 23 ± 15 g protein/day were offered. Mean daily energy intake increased by 207 (95%CI 47–368, p = 0.005) kcal and protein intake by 14 (7–21, p < 0.001) g (w12 vs w1). Quality of life (QoL) increased in the subscale “care relationship” (+ 9 (3–15) points, p = 0.002, w12 vs w6). Body weight, handgrip strength, and other QoL subscales did not change. Conclusion: Our intervention improved dietary intake and one QoL subscale in NH residents with (risk of) malnutrition. As a next step, randomized controlled trials are needed to investigate the impact of individualised interventions more comprehensively.
CRIS-Team Scopus Importer:2021-12-10
Keywords: Energy intake; Food supplements; Individualised; Malnutrition; Nursing home; Nutritional intervention

Narrative review of low-intake dehydration in older adults - Beck, Anne Marie; Seemer, Johanna; Knudsen, Anne Wilkens; Munk, Tina (Nutrients, 2021)
Low-intake dehydration is a common and often chronic condition in older adults. Adverse health outcomes associated with low-intake dehydration in older adults include poorer cognitive performance, reduced quality of life, worsened course of illness and recovery, and a high number of unplanned hospital admissions and increased mortality. The subjective methods to assess (risk of) dehydration are not reliable, and the evidence about preventive measures are also limited. So is the knowledge about the optimal intake of beverages per day. This narrative review presents the state of the science on the role of low intake hydration in older adults. Despite its simple cause—the inadequate intake of beverages—low-intake dehydration appears to be a very complex problem to address and much more research is needed in the area. Based on the existing evidence, it seems necessary to take setting specific differences and individual problems and needs into account to tackle dehydration in older adults. Further, it is necessary to increase awareness of the prevalence and severity of low-intake dehydration among older adults and in nursing staff in care homes and hospitals as well as among caregivers of older adults living at home.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Drinks; Hydration; Interventions; Osmolality; Osmolarity

Usual protein intake amount and sources of nursing home residents with (Risk of) malnutrition and effects of an individualized nutritional intervention: An enable study - Seemer, Johanna; Volkert, Dorothee; Fleckenstein-Sußmann, Daniela; Bader-Mittermaier, Stephanie; Sieber, Cornel; Kiesswetter, Eva (Nutrients, 2021)
Nursing home (NH) residents with (risk of) malnutrition are at particular risk of low protein intake (PI). The aim of the present analysis was (1) to characterize usual PI (total amount/day (d) and meal, sources/d and meal) of NH residents with (risk of) malnutrition and (2) to evaluate the effects of an individualized nutritional intervention on usual PI. Forty residents (75% female, 85 ± 8 years) with (risk of) malnutrition and inadequate dietary intake received 6 weeks of usual care followed by 6 weeks of intervention. During the intervention phase, an additional 29 ± 11 g/d from a protein-energy drink and/or 2 protein creams were offered to compensate for individual energy and/or protein deficiencies. PI was assessed with two 3-day-weighing records in each phase and assigned to 4 meals and 12 sources. During the usual care phase, mean PI was 41 ± 10 g/d. Lunch and dinner contributed 31 ± 11% and 32 ± 9% to daily intake, respectively. Dairy products (median 9 (interquartile range 6–14) g/d), starchy foods (7 (5–10) g/d) and meat/meat products (6 (3–9) g/d) were the main protein sources in usual PI. During the intervention phase, an additional 18 ± 10 g/d were consumed. Daily PI from usual sources did not differ between usual care and intervention phase (41 ± 10 g/d vs. 42 ± 11 g/d, p = 0.434). In conclusion, daily and per meal PI were very low in NH residents with (risk of) malnutrition, highlighting the importance of adequate intervention strategies. An individualized intervention successfully increased PI without affecting protein intake from usual sources.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Food source; Individualized intervention; Malnutrition; Nursing home; Protein intake